2012
DOI: 10.1099/jmm.0.034025-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia psittaci in the feral pigeon population of Basel, Switzerland

Abstract: Feral pigeons (Columba livia) are commonly infected with Chlamydia psittaci, the agent of psittacosis in humans. To assess the risk of zoonosis posed by feral pigeons in the urban environment, we determined the prevalence of Chlamydia psittaci by detection of the outermembrane protein A (ompA) gene of this pathogen in pharyngeal and cloacal samples of 202 feral pigeons present in a loft in Basel, Switzerland. Additionally, we examined 620 fresh faecal droppings of feral pigeons at six public sites in Basel. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
2
26
1
3
Order By: Relevance
“…The zoonotic incidence of C. psittaci and C. abortus is well documented, but their incidence in human diseases might be underestimated (Braukmann et al, 2012;Geigenfeind et al, 2012). In particular, *50 % of pneumonia cases remain diagnosed as of unknown aetiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zoonotic incidence of C. psittaci and C. abortus is well documented, but their incidence in human diseases might be underestimated (Braukmann et al, 2012;Geigenfeind et al, 2012). In particular, *50 % of pneumonia cases remain diagnosed as of unknown aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…C. psittaci is responsible worldwide for respiratory tract infections ranging from benign illness to severe pneumoniae with fatal outcomes. The primary reservoir of C. psittaci is birds, in particular parrots and parakeets (Longbottom & Coulter, 2003), but recent studies on chicken from the food industries and on feral pigeons suggest a significant prevalence of C. psittaci in these animals as well (Magnino et al, 2009;Geigenfeind et al, 2012;Yin et al, 2013). Transmission between birds is primarily achieved through the inhalation of aerosols containing desiccated infectious particles originating from contaminated birds faeces.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2010). A utilização de amostras de fezes para o diagnóstico de C. psittaci provavelmente subestima o status de infecção de uma população, em virtude de a bactéria ser eliminada de forma intermitente nas fezes das aves infectadas (Geigenfeind et al, 2012), o que pode contribuir para a ocorrência de resultados falsos negativos. A coleta de amostras em diferentes sítios, como amostras de orofaringe e cloaca, e em momentos diferentes aumenta a chance de diagnóstico de infecção por C. psittaci (Andersen, 1996).…”
Section: Methodsunclassified
“…Restringir o acesso dessas aves aos possíveis locais de abrigo e nidificação, bem como impedir o fornecimento de alimentos e promover a correta destinação dos resíduos orgânicos produzidos nas cidades, tem sido algumas das medidas adotadas para o controle populacional dos pombos (Nunes, 2003). A redução sustentável da população de pombos tem efeito benéfico no status de saúde dessas aves (Geigenfeind et al, 2012). Atualmente, a presença de grandes populações de pombos nos centros urbanos representa um grave problema de saúde pública.…”
unclassified
“…In our study, however, the infection rate was higher and breeding activity was observed all year round. On the other hand, Geigenfeind et al (2012) detected C. psittaci DNA only in 8.4% (17/202) of feral pigeons of all ages living in a pigeon loft in the city of Basel, Switzerland. It should be mentioned that this city has an ongoing project since the 1980s with the aim of establishing a small, but healthy population of feral pigeons.…”
Section: Screening Of Feral Pigeons (Columba Livia) For Pathogens Of mentioning
confidence: 99%